Tính đạo hàm của các hàm số sau:
a) \(y = \frac{{\sqrt x }}{{x + 1}};\)
b) \(y = \left( {\sqrt x + 1} \right)\left( {{x^2} + 2} \right).\)
Tính đạo hàm của các hàm số sau:
a) \(y = {\left( {\frac{{2x - 1}}{{x + 2}}} \right)^5}\)
b) \(y = \frac{{2x}}{{{x^2} + 1}}\);
c) \(y = {e^x}{\sin ^2}x\);
d) \(y = \log (x + \sqrt x )\).
tham khảo:
a)\(y'\left(x\right)=5\left(\dfrac{2x-1}{x+2}\right)^4.\dfrac{\left(x+2\right)\left(2\right)-\left(2x-1\right).1}{\left(x+2\right)^2}\)
\(=\dfrac{10\left(2x-1\right)\left(x+2\right)^3}{\left(x+2\right)^4}=\dfrac{20x-50}{\left(x+2\right)^4}\)
b)\(y'\left(x\right)=\dfrac{2\left(x^2+1\right)-2x\left(2x\right)}{\left(x^2+1\right)^2}\)\(=\dfrac{2\left(1-x^2\right)}{\left(x^2+1\right)^2}\)
c)\(y'\left(x\right)=e^x.2sinxcosx+e^xsin^2x.2cosx\)
\(=2e^xsinx\left(cosx+sinxcosx\right)\)
\(=2e^xsinxcos^2x\)
d)\(y'\left(x\right)=\dfrac{1}{x\sqrt{x}}.\left(+\dfrac{1}{2\sqrt{x}}\right)\)
\(=\dfrac{1}{\sqrt{x}\left(2\sqrt{x}+\sqrt{x}+2\right)}\)
\(=\dfrac{1}{\sqrt{x}\left(3\sqrt{x}+2\right)}\)
Tính đạo hàm của các hàm số sau:
a) \(y = \frac{{2x - 1}}{{x + 2}};\)
b) \(y = \frac{{2x}}{{{x^2} + 1}}.\)
tham khảo:
a)\(y'=\dfrac{\left(2\right)\left(x+2\right)-\left(2x-1\right)\left(1\right)}{\left(x+2\right)^2}\)
\(y'=\dfrac{5}{\left(x+2\right)^2}\)
b)\(y'=\dfrac{\left(2\right)\left(x^2+1\right)-\left(2x\right)\left(2x\right)}{\left(x^2+1\right)^2}\)
\(y'=\dfrac{2\left(1-x^2\right)}{\left(x^2+1\right)^2}\)
Tính đạo hàm của các hàm số sau:
a) \(y = 2{{\rm{x}}^3} - \frac{{{x^2}}}{2} + 4{\rm{x}} - \frac{1}{3}\);
b) \(y = \frac{{ - 2{\rm{x}} + 3}}{{{\rm{x}} - 4}}\);
c) \(y = \frac{{{x^2} - 2{\rm{x}} + 3}}{{{\rm{x}} - 1}}\); d) \(y = \sqrt {5{\rm{x}}} \).
a) \(y' = 2.3{{\rm{x}}^2} - \frac{1}{2}.2{\rm{x}} + 4.1 - 0 = 6{{\rm{x}}^2} - x + 4\).
b) \(y' = \frac{{{{\left( { - 2{\rm{x}} + 3} \right)}^\prime }.\left( {{\rm{x}} - 4} \right) - \left( { - 2{\rm{x}} + 3} \right).{{\left( {{\rm{x}} - 4} \right)}^\prime }}}{{{{\left( {{\rm{x}} - 4} \right)}^2}}}\)
\( = \frac{{ - 2\left( {{\rm{x}} - 4} \right) - \left( { - 2{\rm{x}} + 3} \right).1}}{{{{\left( {{\rm{x}} - 4} \right)}^2}}}\)
\( = \frac{{ - 2{\rm{x}} + 8 + 2{\rm{x}} - 3}}{{{{\left( {{\rm{x}} - 4} \right)}^2}}} = \frac{5}{{{{\left( {{\rm{x}} - 4} \right)}^2}}}\)
c) \(y' = \frac{{{{\left( {{x^2} - 2{\rm{x}} + 3} \right)}^\prime }\left( {{\rm{x}} - 1} \right) - \left( {{x^2} - 2{\rm{x}} + 3} \right){{\left( {{\rm{x}} - 1} \right)}^\prime }}}{{{{\left( {{\rm{x}} - 1} \right)}^2}}}\)
\( = \frac{{\left( {2{\rm{x}} - 2} \right)\left( {{\rm{x}} - 1} \right) - \left( {{x^2} - 2{\rm{x}} + 3} \right).1}}{{{{\left( {{\rm{x}} - 1} \right)}^2}}}\) \( = \frac{{2{{\rm{x}}^2} - 2{\rm{x}} - 2{\rm{x}} + 2 - {x^2} + 2{\rm{x}} - 3}}{{{{\left( {{\rm{x}} - 1} \right)}^2}}}\)
\( = \frac{{{x^2} - 2{\rm{x}} - 1}}{{{{\left( {{\rm{x}} - 1} \right)}^2}}}\)
d) \(y' = {\left( {\sqrt 5 .\sqrt x } \right)^\prime } = \sqrt 5 .\frac{1}{{2\sqrt x }} = \frac{{\sqrt 5 }}{{2\sqrt x }} = \frac{5}{{2\sqrt {5x} }}\).
Tính đạo hàm của các hàm số sau:
a) \(y = {x^3} - 3{x^2} + 2x + 1;\)
b) \(y = {x^2} - 4\sqrt x + 3.\)
tham khảo:
a)\(y'=\dfrac{d}{dx}\left(x^3\right)-\dfrac{d}{dx}\left(3x^2\right)+\dfrac{d}{dx}\left(2x\right)+\dfrac{d}{dx}\left(1\right)\)
\(y'=3x^2-6x+2\)
b)\(\dfrac{d}{dx}\left(x^n\right)=nx^{n-1}\)
\(\dfrac{d}{dx}\left(\sqrt{x}\right)=\dfrac{1}{2\sqrt{x}}\)
\(\dfrac{d}{dx}\left(f\left(x\right)+g\left(x\right)\right)=f'\left(x\right)+g'\left(x\right)\)
\(\dfrac{d}{dx}\left(cf\left(x\right)\right)=cf'\left(x\right)\)
\(y'=\dfrac{d}{dx}\left(x^2\right)-\dfrac{d}{dx}\left(4\sqrt{x}\right)+\dfrac{d}{dx}\left(3\right)\)
\(y'=2x-2\sqrt{x}\)
Tính các đạo hàm của hàm số sau:
a) \(y=\sqrt{x}\left(x+3\right)\)
b) \(y=\sqrt{2x^2-6x-9}\)
c) \(y=\left(\sqrt{x^2+1}+x\right)^{10}\)
Tính đạo hàm của các hàm số sau:
a) \(y = {\left( {2x - 3} \right)^{10}};\)
b) \(y = \sqrt {1 - {x^2}} .\)
\(a,y'=\left[\left(2x-3\right)^{10}\right]'\\ =10\left(2x-3\right)^9\left(2x-3\right)'\\ =20\left(2x-3\right)^9\\ b,y'=\left(\sqrt{1-x^2}\right)'\\ =\dfrac{\left(1-x^2\right)'}{2\sqrt{1-x^2}}\\ =-\dfrac{2x}{2\sqrt{1-x^2}}\\ =-\dfrac{x}{\sqrt{1-x^2}}\)
Tính đạo hàm của các hàm số sau:
a) \(y=x^4-\dfrac{3}{x}+\sqrt{x}-\dfrac{1}{x^2}\)
b) \(y=\dfrac{4sinx-3}{7-5sinx}\)
a.
\(y'=4x^3+\dfrac{3}{x^2}+\dfrac{1}{2\sqrt{x}}+\dfrac{2}{x^3}\)
b.
\(y'=\dfrac{\left(4sinx-3\right)'.\left(7-5sinx\right)-\left(7-5sinx\right)'.\left(4sinx-3\right)}{\left(7-5sinx\right)^2}\)
\(=\dfrac{4cosx\left(7-5sinx\right)+5cosx\left(4sinx-3\right)}{\left(7-5sinx\right)^2}\)
\(=\dfrac{13cosx}{\left(7-5sinx\right)^2}\)
Tính đạo hàm của các hàm số sau:
a. \(y=x.\sqrt{x^2-2x}\)
b.\(y=3sin2x+cos3x\)
Giúp mk vs ạ!!!
a.\(y'=x\left(\sqrt{x^2-2x}\right)'+\sqrt{x^2-2x}=\dfrac{x}{2\sqrt{x^2-2x}}2\left(x-1\right)+\sqrt{x^2-2x}=\dfrac{x\left(x-1\right)}{\sqrt{x^2-2x}}+\sqrt{x^2-2x}\)
\(=\dfrac{x^2-x+x^2-2x}{2\sqrt{x^2-2x}}=\dfrac{2x^2-3x}{2\sqrt{x^2-2x}}\)
b. \(y=3sin2x+cos3x\Rightarrow y'=6cos2x-3sin3x\)
Tính đạo hàm của các hàm số sau:
a) \(y = (2x^2 - x + 1)^{\frac{1}{3}}\)
b) \(y = (3x+1)^{\pi}\)
c) \(y = \sqrt[3]{\dfrac{1}{x-1}}\)
d) \(y =\log_{3} \left(\dfrac{x+1}{x-1}\right)\)
e) \(y = 3^{x^{2}}\)
f) \(y = \left(\dfrac{1}{2}\right)^{x^2-1}\)
h) \(y = (x+1) . e^{cosx}\)
g) \(y = \ln (x^2+x+1)\)
l) \(y = \dfrac{\ln x}{x+1}\)
a: \(y=\left(2x^2-x+1\right)^{\dfrac{1}{3}}\)
=>\(y'=\dfrac{1}{3}\left(2x^2-x+1\right)^{\dfrac{1}{3}-1}\cdot\left(2x^2-x+1\right)'\)
\(=\dfrac{1}{3}\cdot\left(4x-1\right)\left(2x^2-x+1\right)^{-\dfrac{2}{3}}\)
b: \(y=\left(3x+1\right)^{\Omega}\)
=>\(y'=\Omega\cdot\left(3x+1\right)'\cdot\left(3x+1\right)^{\Omega-1}\)
=>\(y'=3\Omega\left(3x+1\right)^{\Omega-1}\)
c: \(y=\sqrt[3]{\dfrac{1}{x-1}}\)
=>\(y'=\dfrac{\left(\dfrac{1}{x-1}\right)'}{3\cdot\sqrt[3]{\left(\dfrac{1}{x-1}\right)^2}}\)
\(=\dfrac{\dfrac{1'\left(x-1\right)-\left(x-1\right)'\cdot1}{\left(x-1\right)^2}}{\dfrac{3}{\sqrt[3]{\left(x-1\right)^2}}}\)
\(=\dfrac{-x}{\left(x-1\right)^2}\cdot\dfrac{\sqrt[3]{\left(x-1\right)^2}}{3}\)
\(=\dfrac{-x}{\sqrt[3]{\left(x-1\right)^4}\cdot3}\)
d: \(y=log_3\left(\dfrac{x+1}{x-1}\right)\)
\(\Leftrightarrow y'=\dfrac{\left(\dfrac{x+1}{x-1}\right)'}{\dfrac{x+1}{x-1}\cdot ln3}\)
\(\Leftrightarrow y'=\dfrac{\left(x+1\right)'\left(x-1\right)-\left(x+1\right)\left(x-1\right)'}{\left(x-1\right)^2}:\dfrac{ln3\left(x+1\right)}{x-1}\)
\(\Leftrightarrow y'=\dfrac{x-1-x-1}{\left(x-1\right)^2}\cdot\dfrac{x-1}{ln3\cdot\left(x+1\right)}\)
\(\Leftrightarrow y'=\dfrac{-2}{\left(x-1\right)\cdot\left(x+1\right)\cdot ln3}\)
e: \(y=3^{x^2}\)
=>\(y'=\left(x^2\right)'\cdot ln3\cdot3^{x^2}=2x\cdot ln3\cdot3^{x^2}\)
f: \(y=\left(\dfrac{1}{2}\right)^{x^2-1}\)
=>\(y'=\left(x^2-1\right)'\cdot ln\left(\dfrac{1}{2}\right)\cdot\left(\dfrac{1}{2}\right)^{x^2-1}=2x\cdot ln\left(\dfrac{1}{2}\right)\cdot\left(\dfrac{1}{2}\right)^{x^2-1}\)
h: \(y=\left(x+1\right)\cdot e^{cosx}\)
=>\(y'=\left(x+1\right)'\cdot e^{cosx}+\left(x+1\right)\cdot\left(e^{cosx}\right)'\)
=>\(y'=e^{cosx}+\left(x+1\right)\cdot\left(cosx\right)'\cdot e^u\)
\(=e^{cosx}+\left(x+1\right)\cdot\left(-sinx\right)\cdot e^u\)
a) \(y=\left(2x^2-x+1\right)^{\dfrac{1}{3}}\)
\(\Rightarrow y'=\dfrac{1}{3}.\left(2x^2-x+1\right)^{\dfrac{1}{3}-1}.\left(4x-1\right)\)
\(\Rightarrow y'=\dfrac{1}{3}.\left(2x^2-x+1\right)^{-\dfrac{2}{3}}.\left(4x-1\right)\)
b) \(y=\left(3x+1\right)^{\pi}\)
\(\Rightarrow y'=\pi.\left(3x+1\right)^{\pi-1}.3=3\pi.\left(3x+1\right)^{\pi-1}\)
c) \(y=\sqrt[3]{\dfrac{1}{x-1}}\)
\(\Rightarrow y'=\dfrac{\left(x-1\right)^{-1-1}}{3\sqrt[3]{\left(\dfrac{1}{x-1}\right)^{3-1}}}=\dfrac{\left(x-1\right)^{-2}}{3\sqrt[3]{\left(\dfrac{1}{x-1}\right)^2}}=\dfrac{1}{3.\sqrt[]{x-1}.\sqrt[3]{\left(\dfrac{1}{x-1}\right)^2}}\)
\(\Rightarrow y'=\dfrac{1}{3\left(x-1\right)^{\dfrac{1}{2}}.\left(x-1\right)^{\dfrac{2}{3}}}=\dfrac{1}{3\left(x-1\right)^{\dfrac{7}{6}}}=\dfrac{1}{3\sqrt[6]{\left(x-1\right)^7}}\)
d) \(y=\log_3\left(\dfrac{x+1}{x-1}\right)\)
\(\Rightarrow y'=\dfrac{\dfrac{1-\left(-1\right)}{\left(x-1\right)^2}}{\dfrac{x+1}{x-1}.\ln3}=\dfrac{2}{\left(x+1\right)\left(x-1\right).\ln3}\)
e) \(y=3^{x^2}\)
\(\Rightarrow y'=3^{x^2}.ln3.2x=2x.3^{x^2}.ln3\)
f) \(y=\left(\dfrac{1}{2}\right)^{x^2-1}\)
\(\Rightarrow y'=\left(\dfrac{1}{2}\right)^{x^2-1}.ln\dfrac{1}{2}.2x=2x.\left(\dfrac{1}{2}\right)^{x^2-1}.ln\dfrac{1}{2}\)
Các bài còn lại bạn tự làm nhé!